The Land's Greatest Treasure: Social Roles and Female - Doumi Alima; biki Djouhaina (University of El-Oued جامعة الوادي, 2025)
الملخص: تعتبر النساء االفغانيات كنزا عظيما المتهن، فقد استحوذن على اهتمام دولي بفضل صمودهن وقدرتهن على تحدي الظروف القاسية. تكشف هذه الدراسة عن األدوار االجتماعية لإلناث في المجتمع األفغاني، باستخدام فيلم المعيل )2017 ) كدراسة حالة الستكشاف تصوير األدوار االجتماعية لإلناث وردود أفعالهن تحت سيطرة طالبان. تعتمد هذه الدراسة على منهجية الخطاب النقدي النوعي لمعالجة أسئلة البحث واكتساب فهم شامل لألدوار االجتماعية للجنسين. تحلل منهجية الخطاب النقدي اللغة وعالقتها بالسياق األفغاني. تهدف هذه األطروحة إلى إبراز التجارب االجتماعية للمرأة األفغانية واستكشاف كيف تعكس سرديات الفيلم وجهات النظر االجتماعية تجاه المرأة األفغانية من خالل التركيز على تصوير األدوار االجتماعية لإلناث في الفيلم. يتضمن الفصل النظري تعريفات للجنس والنوع واألدواراالجتماعية، مع التركيز على وجهات النظر الشرقية والغربية. كما يتناول الفصل التطبيقي األدوار االجتماعية األنثوية في فيلم المعيل )2017 ،)حيث تتحدى بطلة الفيلم بارفانا ووالدتها األعراف الجندرية المفروضة، بينما تُصَّور أختها كشخصية خاضعة ومقيدة بحكم طالبان. بناءا على ذلك، يُظهر هذا البحث أن النساء األفغانيات قادرات على القيام بشتى األدوار حتى التي طالما كانت حكرا على الرجال. كما يظهر الفيلم ان النساء لهن القدرة على التحول من رعاية االسرة الى اعالتها. Résumé : فرنسية أو انجلزية Afghan women have captured international attention with their resilience and ability to Challenge restrictive conditions. This study unveils female social roles in Afghan Society, using The Breadwinner (2017) as a case study to explore the portrayal of female Social roles and their reactions under Taliban control. This study uses a qualitative Critical discourse analysis lens to address the research questions and gain a thorough Understanding of gender social roles. The critical discourse method examines language In relation to the Afghan context. The aim of this dissertation is to bring to the surface The Afghan women’s social experiences and to explore how the film’s narratives reflect Social views toward Afghan women by focusing on the portrayal of female social roles In the film. The theoretical chapter provides definitions of sex, gender, and social roles, Focusing on Eastern and Western perspectives. The practical chapter examines the Representation of female social roles in The Breadwinner (2017), in which the Protagonist Parvana and her mother challenge the imposed gender norms, while her Sister is depicted as a submissive, passive character restricted by the Taliban rule. Therefore, this research shows that Afghan women are able to navigate multiple roles, Even those assigned to men. Women are shown switching roles from household Caregivers to family breadwinners.
Characters in The Breadwinner (2017)
Master's Degree In Literature and Civilization
Keywords: المرأة األفغانية، النوع االجتماعي، عدم االستقرار السياسي، الدور االجتماعي، المعيل; Afghan women; Gender; Political Instability; Social role; The Breadwinner